Enhancing Emotional Labor Management and Perceived Control Through Mindfulness: A Randomized Controlled Trial - McDonnell, Maura; Rostami, Mehdi (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to evaluate the effectiveness of a structured mindfulness intervention in reducing emotional labor and enhancing perceived control among individuals engaged in high-emotional labor roles. Given the growing prevalence of emotional labor in various professions, this study seeks to provide evidence-based insights into the potential benefits of mindfulness practices for psychological well-being and job performance. A randomized controlled trial design was employed with 30 participants randomly assigned to either the intervention group or the control group, each consisting of 15 participants. The intervention group underwent ten 75-minute mindfulness training sessions over ten weeks, while the control group received no intervention. Emotional labor and perceived control were assessed at three time points: pre-intervention, post-intervention, and five-month follow-up. Data were analyzed using SPSS version 27, with analysis of variance (ANOVA) with repeated measurements and Bonferroni post-hoc tests applied to determine the significance of the results. The results indicated significant reductions in emotional labor and significant improvements in perceived control in the intervention group compared to the control group, both immediately post-intervention and at the five-month follow-up. Participants in the mindfulness training reported lower levels of emotional dissonance and higher levels of emotional regulation and perceived control. These findings highlight the potential of mindfulness training to mitigate the adverse effects of emotional labor and promote long-term psychological resilience and well-being. Mindfulness training proved to be an effective intervention for reducing emotional labor and enhancing perceived control among individuals in high-emotional labor roles. The sustained benefits observed at the five-month follow-up suggest that mindfulness practices can lead to lasting improvements in emotional regulation and psychological health. Organizations should consider integrating mindfulness training into employee development programs to support a healthier and more resilient workforce.